Embedding power system's reliability within a long-term Energy System Optimization Model: Linking high renewable energy integration and future grid stability for France by 2050. (1st January 2020) - Seck, Gondia Sokhna; Krakowski, Vincent; Assoumou, Edi; Maïzi, Nadia; Mazauric, Vincent
Highlights: First integration of system adequacy and transient stability in French energy model. Power capacity doubles in 100% renewable scenario compared to the reference by 2050. Max of 65% Variable Renewable Energy in the installed capacity for a reliable grid. The grid stability is maintained using additional back-up and flexible options. Results shed light on the importance of power exchanges with neighbouring countries. Abstract: The aim of this article is to take into account short-term power grid operation conditions in long-term prospective analysis in the case of France. It is the first time that the integration of system adequacy and transient stability has been achieved in prospective studies for an electro intensive country, following studies conducted on Reunion Island. The methodology relies on a quantitative assessment of the French power sector's reliability through an endogenous definition of a reliability indicator related to kinetic reserves into an Energy System Optimization Model (ESOM), TIMES-FR model. The result gives an overview of how the stability of the grid is maintained with an increasing share of renewables using additional back-up and flexible options. We observe that it is technically possible to achieve around 65% of Variable Renewable Energy sources (VREs) in the installed capacity without impairing the reliability of the system. In more detail, the maximum VRE in total hourly power production that complies with the reliability constraint was assessed as around 84% in the 100 EnR scenario. However, in order to guarantee this system reliability, the cumulated new installed capacity, in a scenario with 100% renewable energy sources (RES) in the power mix, would represent the double of the Business-As-Usual (BAU) scenario over the period 2013–2050. Therefore, major upstream planning would be needed, and that more flexible options i.e. demand-response, storage technologies and interconnections or substitute or additional plants should be considered to satisfy the reliability constraint at any time by providing extra inertia to the system. This modelling exercise shows the importance of power exchanges with neighbours with higher share of RE in the power production.